2021
DOI: 10.3390/md19010036
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of 3D Printed Chitosan/Pectin Constructs for Biomedical Applications

Abstract: In the present study, chitosan (CS) and pectin (PEC) were utilized for the preparation of 3D printable inks through pneumatic extrusion for biomedical applications. CS is a polysaccharide with beneficial properties; however, its printing behavior is not satisfying, rendering the addition of a thickening agent necessary, i.e., PEC. The influence of PEC in the prepared inks was assessed through rheological measurements, altering the viscosity of the inks to be suitable for 3D printing. 3D printing conditions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 83 publications
(57 reference statements)
1
19
1
Order By: Relevance
“…Many features such as cytotoxicity, mechanical properties as well as healing efficiencies have to be considered while fabricating a scaffold/substrate for tissue regeneration. Various existing methodologies have been adapted for processing of chitosan‐based nanocomposites into films, 34 fiber‐meshes, 35 hydrogels, 36–40 and 3D printed constructs 41 to mimic the 3D environment of tissues. Processing into a freestanding thin film is the easiest choice and affordable route to evaluate the physico‐mechanical properties and biocompatibility of the designed nanocomposites 42–44 .…”
Section: Chitosan‐based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…Many features such as cytotoxicity, mechanical properties as well as healing efficiencies have to be considered while fabricating a scaffold/substrate for tissue regeneration. Various existing methodologies have been adapted for processing of chitosan‐based nanocomposites into films, 34 fiber‐meshes, 35 hydrogels, 36–40 and 3D printed constructs 41 to mimic the 3D environment of tissues. Processing into a freestanding thin film is the easiest choice and affordable route to evaluate the physico‐mechanical properties and biocompatibility of the designed nanocomposites 42–44 .…”
Section: Chitosan‐based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…The three hydrogels reached very fast (less than 30 min) and very high swelling values (between 1500 and 2000%) in both formulations with and without DMEM, faster and higher values than similar Ch-Pe systems proposed by other authors that reported lower swelling ratio values (about 370% [ 27 ], 150–200% [ 40 ] or slower [ 15 ]) [ 14 , 29 , 31 , 41 ]. Regarding the in vitro stability, tested up to 25 days, hydrogels without DMEM were stable up to 25 days, except for the Ch-Pec-PB samples that completely degraded after 7 days.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we aimed at developing a chitosan/pectin hydrogel system suitable for cell embedding and culturing, meeting, therefore, some fundamental chemico-physical requirements, such as (i) a physiological pH, (ii) injectability at r.t. and (iii) ability to gel at the physiological temperature, i.e., 37 °C. Several hydrogels with chitosan and pectin have been proposed in the literature; however, they are usually in the gel state at r.t. and in the sol state at high temperatures used to solubilize the two polymers (60 to 97 °C), conditions not suitable for cell viability [ 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. To overcome the limits of the chitosan/pectin systems reported in the literature, not compatible with cell embedding applications, in the present study, we decided to exploit the well-known ability of chitosan solution to gel at 37 °C thanks to the addition of weak bases such as βGP, in order to induce the formation of a chitosan hydrogel network that incorporates pectin inside, giving rise to a semi-IPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to sodium alginate, due to its carboxylic groups, pectin forms polyelectrolyte complexes with CS. Michailidou et al assessed the printability of CS/Pec hydrogels [133]. The addition of Pec increased significantly the viscosity of the CS/Pec hydrogels and consequently improved the shape fidelity of the printed constructs.…”
Section: Extrusion-based Printing Of Chitosan Inksmentioning
confidence: 99%